2014
DOI: 10.1371/journal.pone.0098348
|View full text |Cite
|
Sign up to set email alerts
|

Oral Medicines for Children in the European Paediatric Investigation Plans

Abstract: IntroductionPharmaceutical industry is no longer allowed to develop new medicines for use in adults only, as the 2007 Paediatric Regulation requires children to be considered also. The plans for such paediatric development called Paediatric Investigation Plans (PIPs) are subject to agreement by the European Medicines Agency (EMA) and its Paediatric Committee (PDCO). The aim of this study was to evaluate the key characteristics of oral paediatric medicines in the PIPs and the changes implemented as a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In a review of approved PIPs for children aged 0–11 years, 37 approved PIPs for monolithic tablets were reported . Size data were available on 24 of these tablets, where two were small (0–4 mm), 15 were medium‐sized (5–9 mm) and four were large (>10 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of approved PIPs for children aged 0–11 years, 37 approved PIPs for monolithic tablets were reported . Size data were available on 24 of these tablets, where two were small (0–4 mm), 15 were medium‐sized (5–9 mm) and four were large (>10 mm).…”
Section: Discussionmentioning
confidence: 99%
“…There was little information on how age correlated to tablet size within this article although it was stated that two PIPs have been agreed with tablets from 0 to 4 mm for children aged 2–5 years. The shape of tablets in approved PIPs was reported for 21 of the 37 approved monolithic tablets, 12 were round, eight were oblong/caplet/oval and 1 was a specified other shape …”
Section: Discussionmentioning
confidence: 99%
“…This can lead not only to rejection of the compound (and even therapeutic concept) under study but also, and more insidiously, to questioning of the predictive value of preclinical animal models. Further, additional requirements like the need in the EU for a (pre or postauthorisation) paediatric study, even if well-intended and of long-term benefit, have added further expense and challenges to clinical development (Arango, 2015;Eichler et al, 2013;Stoyanova-Beninska et al, 2011;Van Riet-Nales et al, 2014). This has been taking place in an unfavourable economic climate, and a legal and health service environment where patent protection is of limited duration, the clinical population to be treated will likely be more confined than in the past, and the negotiation of reimbursement with national pricing agencies is increasingly protracted.…”
Section: The Challenge Of Clinically Developing Novel Agents For Cns mentioning
confidence: 99%
“…Following a detailed analysis, we concluded that the PDCO evaluation had resulted in little changes to the company's proposal. Apparently, companies had been able to adequately answer the EMA questions (73). Acknowledging that industry would benefit from readily available and up-todate information on the safety of excipients in children, the EuPFI has established a freely accessible Safety and Toxicity of Excipients for Paediatrics (STEP) database (53).…”
Section: Current Experiencesmentioning
confidence: 99%